FGFR blockade by pemigatinib treats naïve and castration resistant prostate cancer. (1st February 2022) - Chiodelli, Paola; Coltrini, Daniela; Turati, Marta; Cerasuolo, Marianna; Maccarinelli, Federica; Rezzola, Sara; Grillo, Elisabetta; Giacomini, Arianna; Taranto, Sara; Mussi, Silvia; Ligresti, Alessia; Presta, Marco; et al.
Abstract: Prostate cancer (PCa) is a leading cause of cancer mortality in the male population commonly treated with androgen deprivation therapy (ADT) and relapsing as aggressive and androgen-independent castration-resistant prostate cancer (CRPC). In PCa the FGF/FGFR family of growth factors and receptors represents a relevant mediator of cancer growth, tumor-stroma interaction, and a driver of resistance and relapse to ADT. In the present work, we validate the therapeutic efficacy the FDA-approved FGFR inhibitor pemigatinib, in an integrated platform consisting of human and murine PCa cells, and the transgenic multistage TRAMP model of PCa that recapitulates both androgen-dependent and CRPC settings. Our results show for the first time that pemigatinib causes intracellular stress and cell death in PCa cells and prevents tumor growth in vivo and in the multistage model. In addition, the combination of pemigatinib with enzalutamide resulted in long-lasting tumor inhibition and prevention of CRPC relapse in TRAMP mice. These data are confirmed by the implementation of a stochastic mathematical model and in silico simulation. Pemigatinib represents a promising FDA-approved FGFR inhibitor for the treatment of PCa and CRPC alone and in combination with enzalutamide. Highlights: FGFR inhibition fosters intracellular stress in prostate cancer cells. Pemigatinib impairs the growth of naïve prostate cancer in vitro and in vivo Combination of pemigatinib and enzalutamide leads to long term control of CRPC. Pemigatinib should be considered for the treatment of PCa and CRPC.